KETERAMPILAN VOKABULER SOSIAL DAN KESIAPAN MENGAJAR IPS MAHASISWA PGSD STKIP PERSADA KHATULISTIWA SINTANG – KALIMANTAN BARAT - Eliana Yunitha Seran (Jurnal Pesona Dasar, 2017)
The aim of the research is to obtain objective information about social vocabulary skill and competence and the competence of students of Primary School Teacher Education at Persada Khatulistiwa Sintang College of Teacher Training and Education in teaching Social Science. The research applies quantitative method in the form of survey research. It is a population research with the population of 197 people. The result is vocabulary skill and competence of students of Primary School Teacher Education at Persada Khatulistiwa Sintang College of Teacher Training and Education in teaching Social Science – West Kalimantan is 75% from what is expected, with the details as follows: 1) social vocabulary skill and the competence of the students of Primary School Teacher Education at Persada Khatulistiwa Sintang College of Teacher Training and Education in teaching Social Science is considered “good” with the questionnaire’s score at 86.50%. Based on the hypothesis test, the value of t count is larger than the value of t table, which is 18.67 2.35, so that Ho is rejected and Ha is accepted. The suggestion for this research is teachers should become proficient at educative interaction technique because it directly relates to students’ motivation and learning interest. Educative interaction has considerable influence toward learning success.